The Role of Code-switching in Classroom Interaction: A Study in a Malaysian Public University - Nor Fadhilah Ahmad Powzi,; Lina Zainal, (Development in Language Studies, 2025)
Code-switching as a linguistic phenomenon has been extensively studied. However, it remains a grey area of research. This paper presents the findings and discussion of a preliminary study where a survey on code-switching practices in classroom interactions was conducted among the students of a public university in the southern part of Peninsular Malaysia. It is a public university where English Language is its medium of instruction as well as the expected language of interaction. This survey was conducted to find out the usage and frequency of code-switching in classroom teaching and learning as perceived by 420 respondents. Findings indicate that despite English being the medium of instruction at the university, Malay Language was used interchangeably with English Language during classroom interaction. The findings also indicate that the usage of English Language is generally in the category of Intermediate, not High. Apart from that, the findings reveal that the practices of code-switching were quite frequent across the faculties, which ranged from 25% to 53%. This implies that code-switching is a means needed in classroom interaction. An in-depth study exploring the reasons for code-switching as well as the patterns of code-switching is recommended to further understand how it contributes to language learning.